2022
DOI: 10.3390/vaccines10081225
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Coverage and Effectiveness in a School-Based Varicella Outbreak in Jinan Prefecture, Shandong Province

Abstract: Background: Licheng District of Jinan Prefecture reported a school-based varicella outbreak. We conducted an investigation to analyze the epidemiology and scope of the outbreak, determine varicella vaccine coverage on the school campus, and estimate varicella vaccine effectiveness (VE). Methods: In the epidemiological investigation, we determined the attack rate, the clinical manifestations of varicella cases, and histories of prior varicella disease and varicella vaccination. We tested students for presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…However, VarV-1 could not interrupt the transmission of varicella compared to VarV-2. VarV-2 vaccination has become the preferred choice because of the high breakthrough rate of VarV-1 [ 34 ]. The evaluation of the immunogenicity and safety of live attenuated VarV-2 manufactured by China vaccine corporation revealed that varicella virus has good immune persistence for one to three years after initial immunisation.…”
Section: Discussionmentioning
confidence: 99%
“…However, VarV-1 could not interrupt the transmission of varicella compared to VarV-2. VarV-2 vaccination has become the preferred choice because of the high breakthrough rate of VarV-1 [ 34 ]. The evaluation of the immunogenicity and safety of live attenuated VarV-2 manufactured by China vaccine corporation revealed that varicella virus has good immune persistence for one to three years after initial immunisation.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is coverage among school children is important, but also proper vaccination in terms of completeness in primary and boosters were shown to be important to prevent sustained transmission within the school (31,32). Nevertheless, when outbreaks within schools happened, studies also show that vaccination, even a single dose that taken years ago, was able to protect children against severe cases of disease (33).…”
Section: Utilitarianismmentioning
confidence: 99%
“…Live-attenuated varicella vaccines were introduced in China in 1997 and have been recommended for children 12 months through 12 years old with a single-dose regimen [ 6 ]. However, the national strategy for varicella vaccination in China is to encourage people to receive the vaccine through the principle of voluntarism, and a meta-analysis showed that the overall one-dose varicella vaccine coverage was 61.1%, ranging from 20.8% to 97.8% [ 7 ]. With moderate vaccination coverage, the incidence of varicella increased from 3.17 per 100,000 in 2005 to 70.14 per 100,000 in 2019 [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%